Interaction of DNA with Cu(II) and Co(II) Complexes with Fused Aromatic N-Containing Ligand - Lashanizadegan, M.; Shekarsaraii, S. (Asian Journal of Chemistry, 2012)
Three new complexes of fused aromatic N-containing ligands such as [CuL]Cl2 (1) and [CoL]Br2 (2) (L = 3,10-bis(2-(p-nitrophenyl))-1,3,5,8,10,13-hexaazacyclotetradecane) and [CuL1]Cl2 (3) [L1 = 3,10-bi-phenyl-1,3,5,8,10,13-hexaazacyclotetradecane) have been synthesized and characterized by UV-VIS and IR spectra. The interactions of DNA with [CuL]Cl2, [CoL]Br2 and [CuL1]Cl2 complexes in 1 mM Tris-HCl aqueous neutral complex-DNA molar ratio have been carried out by UV absorption spectrometry and fluorescence spectroscopy. The results support for an intercalative reaction of three complexes with DNA, showing [CuL1]Cl2 has an affinity of ca. 10 times higher than [CuL]Cl2 and [CuL]Cl2 ten times higher than [CoL]Br2.